Soybean meal and Starea (R) blocks compared by wintering cows on bluestem pasture: effects on birth and weaning weights of calves - L.H. Harbers; E.L. Shiawoya; K. Conway; R.M. McKee (Kansas Agricultural Experiment Station Research Reports, 1974)
Similar gains and adjusted weaning weights can be expected from calves whose dams are wintered on soybean meal or Starea protein blocks. Rebreeding time is expected to be similar for both groups of dams.
Keywords: Cattlemen& #x27; s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Soybean meal; Starea; Bluestem pasture; Birth weight; Weaning weight